Theoretical Views of Linguists and Literary Critics on the Term "Linguopoetics" - Komilova Gulmira Olimovna (International Journal on Integrated Education, 2022)
At the end of the 20th century and the beginning of the 21st century, the focus is on research related to the integration of particular sciences. Among the disciplines related to fiction or language, the word, which is a linguistic unit, underlies linguopoetics.